POSTURE DEVIATIONS IN PRACTICING RESISTANCE TRAINING WOMEN - Fernandes, Paulo Sérgio; Venâncio, Patrícia Espindola Mota; Lima, William Alves; Costa, Wesley dos Santos; Maia, Meire de Sousa Moura; Barros, Thais Carvalho; Soares, Viviane (International Journal of Movement Science and Rehabilitation, 2020)
Objective: to evaluate the static posture of practicing resistance training (TR) and to detect the incidence of postural deviations. Materials and Methods: cross-sectional and descriptive study with convenience sample that evaluated 50 women between aged 20-40 practicing resistance training. The anatomical points were marked to take the photograph in anterior, posterior and lateral views. The processing and analysis was performed using free Postural Analysis Software (SAPO). Results: The mean age was 23.26 (7.47) years and the higher deviations were in the spine, (48.3%) with a C-deviation with right thoracolumbar convexity, (17.2 %) women with left shift, lumbar spine slope to the right side in (13.8%) and to the left side in (20.7%). In the right lateral view, half of the had anterioration of the head. Regarding trunk and body alignment, on the right side deviations were observed in 56.0% and 64.0%. Hip anteroversion occurred with 90.0% of those evaluated on the right side and 92% on the left side view. In the lower limbs, valgus knees were present in (42.0%) on the right side and (30.0%) on the left side. Patella deviation and genuflection were found in most participants. The tibiotarsal angle closure showed flat feet in (44%) on the right side and (34%) on the left side. Conclusions: The spine presented deviations that were probably acquired by posture or by muscular imbalances and that can be emphasized by the practice of uncorrected RT. The deviations found in the hip and lower limbs show changes in biomechanics that are risk factors for joint and muscle injuries.